2021
DOI: 10.1177/09564624211048678
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal bacterial load in PrEP users with Mycoplasma genitalium coinfection

Abstract: Objectives Gonococcal infections with a higher bacterial load may pose a higher risk of transmission. We assessed the association between gonococcal bacterial load and coinfection with Mycoplasma genitalium. Methods From September 2015 until May 2018, 200 men and transgender women who have sex with men participated in an HIV pre-exposure prophylaxis (PrEP) demonstration trial in Antwerp, Belgium. They underwent 3-monthly 3-site (anus, urine, and pharynx) molecular testing for N. gonorrhoeae and C. trachomatis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…This is, to the authors' knowledge, the largest study to assess the urogenital MG and CT load simultaneously. Contrary to other studies in NG and HIV, we did not observe a higher MG load with a CT coinfection 6,7 . The high number of patients with a coinfection is, thus, likely because of patient behavioral characteristics, more than bacterial synergistic effects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is, to the authors' knowledge, the largest study to assess the urogenital MG and CT load simultaneously. Contrary to other studies in NG and HIV, we did not observe a higher MG load with a CT coinfection 6,7 . The high number of patients with a coinfection is, thus, likely because of patient behavioral characteristics, more than bacterial synergistic effects.…”
Section: Discussioncontrasting
confidence: 99%
“…4 Chlamydia trachomatis has been implicated in the same clinical syndromes and sequelae as MG. 1,2 Both CT and MG are suggested to increase the transmissibility and acquisition of HIV. 5,6 Also, the small study by Van Dijck et al 7 suggested that the presence of an MG and Neisseria gonorrhoeae (NG) coinfection increased the bacterial load at the anatomical location, possibly impacting gonococcal transmissibility. A higher bacterial load might indicate a higher transmission potential.…”
mentioning
confidence: 99%
“…In a recent HIV pre-exposure prophylaxis (PrEP) demonstration trial involving 200 men, molecular testing for N. gonorrhoeae, C. trachomatis, and M. genitalium found significantly higher gonococcal bacterial loads in the presence of M. genitalium, suggesting that M. genitalium may be a cofactor for N. gonorrhoeae transmission. If this finding is confirmed in other studies, M. genitalium may be required as a cofactor for N. gonorrhoeae transmission in specific populations such as MSM (Van Dijck et al, 2022). Therefore, future studies should investigate co-infections with M. genitalium and other sexually transmitted bacteria (e.g., C. trachomatis or N. gonorrhoeae; Desdorf et al, 2021).…”
Section: Co-infection With Mycoplasma Genitaliummentioning
confidence: 82%